2006
DOI: 10.1002/ffj.1669
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil composition of Leucas milanjiana Guerke

Abstract: A hydrodistilled oil obtained from the leaves of Leucas milanjiana Gurke (Lamiaceae) was analysed by capillary GC and GC-MS. The leaf volatile oil contained 30 components, out of which 26 were identified. The predominant components were found to be β β β β β-cubebene (38.15%), α α α α α-pinene (19.71%), trans-caryophyllene (7.41%) and α α α α α-terpinolene (5.34%). The results are qualitatively and quantitatively at variance with data on other Leucas species and may therefore be of some chemotaxonomic signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The major constituents of other Leucas species viz., L. aspera contains α-farnesene, α-thujene, menthol, amyl propionate, isoamyl propionate [7], 1-octen-3-ol, (E)-caryophyllene and caryophyllene oxide [8]. In other report from L. milanjiana leaves oil has β-cubebene, α-pinene, trans-caryophyllene and α-terpinolene as the major constituents [9]. According to previous bibliography [10][11][12], the presence of β-caryophyllene in essential oils gives them RI=Retention index relative to C 8 -C 25 n-alkanes on BP-1 column, MS=NIST and Wiley library and the literature, t=trace (<0.1%), CI=Co-injection of commercial samples.…”
mentioning
confidence: 99%
“…The major constituents of other Leucas species viz., L. aspera contains α-farnesene, α-thujene, menthol, amyl propionate, isoamyl propionate [7], 1-octen-3-ol, (E)-caryophyllene and caryophyllene oxide [8]. In other report from L. milanjiana leaves oil has β-cubebene, α-pinene, trans-caryophyllene and α-terpinolene as the major constituents [9]. According to previous bibliography [10][11][12], the presence of β-caryophyllene in essential oils gives them RI=Retention index relative to C 8 -C 25 n-alkanes on BP-1 column, MS=NIST and Wiley library and the literature, t=trace (<0.1%), CI=Co-injection of commercial samples.…”
mentioning
confidence: 99%
“…In former studies, the chemical composition of the volatile oils of various Leucas species, e.g., L. virigata , L. aspera , L. indica , L. glabrata , L. milanjiana and L. deflexa , were investigated [ 17 , 18 , 19 , 20 , 21 , 22 ]. We recently reported the chemical content of the volatile oil of the Soqotraen L. virgate , which was distinguished by a high composition of oxygenated monoterpenes (50.8%).…”
Section: Resultsmentioning
confidence: 99%
“…Whereas Joshi (2014) [ 23 ] confirmed the dominance of β-caryophyllene (51.1%) in the L. indica essential oil, Vagionas et al (2007) [ 22 ] found that the fundamental chemical class in L. glabrata is oxygenated monoterpenes (64.4%), with menthone (31.8%) and pulegone (11.4%) as essential constituents. Moreover, high contents of β-cubebene (38.1%), α-pinene (19.7%), and trans-caryophyllene were detected in L. milanjiana oil [ 19 ]. Additionally, the investigation performed on the volatile oil of the L. deflexa leaves revealed a high amount of sesquiterpene hydrocarbons (80.3%) with germacrene- d (27.8%), β-caryophyllene (24.1%) and α-humulene (9.9%) as major components [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…[ 68 ] However, the essential oil fraction from the leaves and flowers of Leucas aspera were found to contain high amount of afarnesene, a-thujene, and menthol;[ 69 70 ] whereas, high content of b- cubebene, a-pinene, trans-caryophyllene, limonene, and a-terpineolene were reported in the essential oil from Leucas milanjiana . [ 71 ] The essential oil fraction of Leucas deflexa leaf was reported to have a high amount of sesquiterpene hydrocarbons, namely, germacrene-D, b- caryophyllene, and a-humulene. [ 72 ] A new type of diterpenes, leucasperones A and B; leucasperols A and B, have been reported from Leucas aspera .…”
Section: Common Compounds Reported In Genus Leucasmentioning
confidence: 99%